Background Adjusted Alignment-Free Dissimilarity Measures Improve the Detection of Horizontal Gene Transfer - Tang, Kujin; Lu, Yang Young; Sun, Fengzhu (Frontiers in Microbiology, 2018)
Horizontal gene transfer (HGT) plays an important role in the evolution of microbial organisms including bacteria. Alignment-free methods based on single genome compositional information have been used to detect HGT. Currently, Manhattan and Euclidean distances based on tetranucleotide frequencies are the most commonly used alignment-free dissimilarity measures to detect HGT. By testing on simulated bacterial sequences and real data sets with known horizontal transferred genomic regions, we found that more advanced alignment-free dissimilarity measures such as $CVTree$ and $d_2^*$ that take into account the background Markov sequences can solve HGT detection problems with significantly improved performance. We also studied the influence of different factors such as evolutionary distance between host and donor sequences, size of sliding window, and host genome composition on the performances of alignment-free methods to detect HGT. Our study showed that alignment-free methods can predict HGT accurately when host and donor genomes are in different order levels. Among all methods, $CVTree$ with word length of 3, $d_2^*$ with word length 3, Markov order 1 and $d_2^*$ with word length 4, Markov order 1 outperform others in terms of their highest $F_1$-score and their robustness under the influence of different factors.